Trade‐induced learning and industrial catch‐up - Mendoza, Ronald U (Archīum Ateneo, 2010)
This article develops a model of trade‐induced learning whereby both domestic and cross‐border learning externalities could drive long‐run growth. This framework is used to synthesise the emerging empirical evidence, revealing how trade‐induced learning could underpin the mechanics behind trade and growth in at least three important ways: first, trading matters, as firms might be able to increase their productivity due to export and import linkages with buyers and suppliers; second, whom you trade with matters, as richer and more technologically advanced trading partners offer more scope for trade‐induced learning; and third, what products you trade matters.